Strategi penerjemahan metafora bahasa Arab ke bahasa Indonesia pada lirik lagu Arab dalam album Aseer Ahsan karya Humood Al-Khuder perspektif Newmark - Asror, M. Khozinatul (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the translation strategy used in translating the metaphors in the album "Aseer Ahsan" by Humood Al-Khuder. The data in this research are metaphors and their translations contained in several songs on the album "Aseer Ahsan". The theory used in this research is Newmark’s metaphor translation strategy. This research is descriptive qualitative in nature with data collection using the method of observing and taking notes. Next, the data analysis technique uses the Miles and Huberman model which includes three stages, namely data reduction, data presentation, and drawing conclusions. The data obtained will be presented along with the results of the translation, then analyzed using Newmark’s theory of metaphor translation strategies, then the final step is drawing conclusions from the results of the analysis. The research results show that there are 32 metaphors that can be translated using seven metaphor translation strategies.